Inherited Thrombocytopenia Caused by Germline Mutation Should Be Considered in Young Patients With Suspected Myelodysplastic Syndrome - Tariq Kewan; Ryan Noss; Lucy A. Godley; Heesun J. Rogers; Hetty E. Carraway (SAGE Publishing, 2020)
Thrombocytopenia 2 (THC2) is an autosomal dominant disorder characterized by ankyrin repeat domain 26 mutation and moderate thrombocytopenia. THC2 exposes patients to a low risk of bleeding and an increased likelihood of myelodysplastic syndrome/acute myeloid leukemia. Germline evaluation for a genetic disorder should be considered when a patient presents with isolated thrombocytopenia and associated dysmegakaryopoiesis. In this case report, we present a male patient who presented with isolated thrombocytopenia but was ultimately confirmed to have an inherited THC2 thrombocytopenia/myelodysplastic syndrome. Given the rarity of the disease, no clear guidelines on how to follow THC2 patients over the long term have been established. We recommend a monthly complete blood count and clinical visits every 3 months at a minimum.